Association between body mass index and cardiometabolic risks among Malay obese adults - Daud, Azlina; Shahadan, Siti Zuhaidah (SAGE Publications Inc., 2019)
Cardiometabolic risk (CMR) is a cluster of risk factors that may predict the occurrence of cardiovascular diseases and diabetes mellitus. This study investigated the association between CMR with body mass index (BMI) among obese adults. The CMRs, including waist circumference, systolic and diastolic blood pressure, blood glucose, total cholesterol, low-density and high-density lipoprotein, triglyceride, and high-sensitivity C-reactive protein (hs-CRP) level, were quantified in 82 obese adults. The findings indicate the highest correlation coefficient value ( r) was .618 between BMI and waist circumference; a weak correlation between mass index and systolic ( r = .276) and diastolic ( r = .311) blood pressure and hs-CRP ( r = .384); and a very weak correlation between BMI level and fasting blood glucose ( r = .069), total cholesterol ( r = .014), low-density lipoprotein (.013), high-density lipoprotein (-.154), and triglyceride (.173). Future strategies for CMR reduction among obese adults should focus on waist circumference and hs-CRP level.